Undifferentiated uterine sarcoma: case report - Zalapa, María F.; Mendoza, Patricio; Holguín, Victoria P.; Leal-González, Raúl (International Journal of Research in Medical Sciences, 2023)
Undifferentiated uterine sarcoma is a rare condition characterized by abnormal bleeding and pelvic pain, which may overlap with the clinical picture of uterine myomatosis. Its presentation is usually chronic and drastically affects the stage at the time of diagnosis. Since it is usually seen in postmenopausal patients, undifferentiated uterine sarcoma presentation in premenopausal patients is rare. We herein report a rare presentation of undifferentiated uterine sarcoma in a 58-year-old Mexican woman, who suffered from progressive pelvic pain for 3 months as well as a 5-day course of postmenopausal bleeding. Study images revealed a pedunculated uterine-mass suggestive of sarcomatous degeneration, accompanied by a left internal iliac necrotic adenopathy, as well as scarce pelvic free fluid. The patient underwent a pelvic tumor and implants resection, total abdominal hysterectomy, bilateral salpingo-oophorectomy, pelvic lymphadenectomy, omentectomy and appendectomy via laparotomy. Despite the therapeutic options for the management of undifferentiated uterine sarcomas described in literature, its survival rate varies between 21% to 68%, when diagnosed on time and depending on if the cancer is localized, regional or distant.